Development of Artificial Intelligence (AI)-Driven Aid to Enhance Visual and Hearing- Impaired Students - Salawa, Joseph Sospeter; Sebastian, Phocas; Nyatega, Charles Okanda; Ally, Juma Said; Karawa, Cuthbert John; Koola, Elizabeth Odrick; Mwanjalila, Richard (African Journal of Education,Science and Technology (AJEST), 2024)
This paper introduces a series of works on Artificial Intelligence (AI)-based assistive devices that improve students’ learning with visual and hearing impairments. Artificial intelligence technology provides personal help and support for various learning tasks and activities. The system uses computer vision techniques to read visual information such as text and images, which can be made available in usable formats such as audio descriptions. In addition, the system can recognize and respond to the user’s voice. commands and requests using speech recognition technologies. Stu- dents can view learning materials, get instant help with classroom activities, and participate in engaging learning exercises designed for their specific needs through an intuitive user interface. Ensuring equal access to educational resources. The project focuses on the effective and efficient teaching and mentoring of students with visual and hearing impairments. To understand the impact and applicability of the proposed AI-based tool in enhancing students with vision or hearing impairments and overall educational engagement, user surveys, and feedback are taken, and it is clear that, to a greater extent, it shows the potential and utility of the system to be included in real-world classroom settings. The importance of this paper is particularly based on the contention that it will bring about a major change as far as education is concerned in a bid to make these noble provisions available for students with disabilities. It speeds up access to the required information, fosters differentiation in delivering the instructions, offers quick help, helps improve academic achievement significantly, and helps learners develop confidence in themselves. Further refinements and extensive user evaluations are ongoing to ensure the system meets the diverse needs of students with visual and hearing impairments.